B(C6F5)3‐Catalyzed α‐Deuteration of Bioactive Carbonyl Compounds with D2O. Issue 2 (11th December 2019) - Chang, Yejin; Myers, Tanner; Wasa, Masayuki
Abstract: An efficient deuteration process of α ‐C−H bonds in various carbonyl‐based pharmaceutical compounds has been developed. Catalytic reactions are initiated by the action of Lewis acidic B(C6 F5 )3 and D2 O, converting a drug molecule into the corresponding boron‐enolate. Ensuing deuteration of the enolate by in situ‐generated D2 O + −H then results in the formation of α ‐deuterated bioactive carbonyl compounds with up to >98% deuterium incorporation. Abstract :